DIGITAL ECONOMICS FOR SOCIAL SUSTAINABILITY: EVIDENCE FROM HUMAN DEVELOPMENT AND POVERTY IN INDONESIAN DISTRICTS - Rofiuddin, Mohammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the impact of the digital economy on human development and poverty in Indonesia using panel data from 514 districts/cities during the period 2022–2024. The Human Development Index (HDI) and poverty rate (P0) are used as dependent variables, while the Digital Society Index (DSI), which covers four pillars: infrastructure and ecosystem, digital skills, digital empowerment, and digital jobs, is used as the main independent variable. Regional economic growth is included as a control variable. Estimations were performed using a panel data regression approach, including the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with Chow, Hausman, and Breusch-Pagan tests used to determine the best model. The results show that the digital economy contributes positively to HDI improvement and poverty reduction. The pillars of digital employment and digital skills have the most significant influence on poverty reduction, while digital infrastructure has a greater influence on HDI improvement. The robustness model with alternative poverty indicators (P1 and P2) reinforces the main findings. These findings emphasize the importance of digital transformation in supporting inclusive development and poverty alleviation. Policy implications are directed at increasing the productive capacity of the poor in the digital ecosystem, making digital transformation a genuine tool for promoting social justice and sustainable development.